Developments in Exercise Capacity Assessment in Heart Failure Clinical Trials and the Rationale for the Design of METEORIC-HF. (3rd March 2022) - Lewis, Gregory D.; Docherty, Kieran F.; Voors, Adriaan A.; Cohen-Solal, Alain; Metra, Marco; Whellan, David J.; Ezekowitz, Justin A.; Ponikowski, Piotr; Böhm, Michael; Teerlink, John R.; Heitner, Stephen B.; Kupfer, Stuart; et al.
Abstract : Heart failure with reduced ejection fraction (HFrEF) is a highly morbid condition for which exercise intolerance is a major manifestation. However, methods to assess exercise capacity in HFrEF vary widely in clinical practice and in trials. We describe advances in exercise capacity assessment in HFrEF and a comparative analysis of how various therapies available for HFrEF impact exercise capacity. Current guideline-directed medical therapy has indirect effects on cardiac performance with minimal impact on measured functional capacity. Omecamtiv mecarbil is a novel selective cardiac myosin activator that directly increases cardiac contractility and in a phase 3 cardiovascular outcomes study significantly reduced the primary composite end point of time to first heart failure event or cardiovascular death in patients with HFrEF. The objective of the METEORIC-HF trial (Multicenter Exercise Tolerance Evaluation of Omecamtiv Mecarbil Related to Increased Contractility in Heart Failure) is to assess the effect of omecamtiv mecarbil versus placebo on multiple components of functional capacity in HFrEF. The primary end point is to test the effect of omecamtiv mecarbil compared with placebo on peak oxygen uptake as measured by cardiopulmonary exercise testing after 20 weeks of treatment. METEORIC-HF will provide state-of-the-art assessment of functional capacity by measuring ventilatory efficiency, circulatory power, ventilatory anaerobic threshold, oxygen uptake recovery kinetics, daily activity, and quality-of-life assessment. Thus, the METEORIC-HF trial will evaluate the potential impact of increased myocardial contractility with omecamtiv mecarbil on multiple important measures of functional capacity in ambulatory patients with symptomatic HFrEF. Registration: URL: https://clinicaltrials.gov ; Unique identifier: NCT03759392.